Students’ Motivations in Choosing English as Additional Course in SMAN 1 Bengkulu - Rama Dahlia; Mulyadi .; Mei Hardiah (Journal of English Education and Teaching, 2019)
The type of this research is Descriptive Quantitative and Qualitative research. It is aimed to find out the motivation which make students in XII Social 6 choose English as an additional subject course and to find out the highest motivation which make students in XII Social 6 choose English as an additional subject course. The subject of this study is the students in class XII social 6 SMAN 1 Kota Bengkulu. In this research, the researcher collected the data by using questionnaire. Then, the data obtained from the questionnaires will be analyzed using SPSS program. The data concerning subjects’ general background as well as their comments will be calculated and presented in percentage. A Likert scale will be used to measure the level and type of subjects’ learning motivation. According to table that the researcher used to analyze extrinsic and intrinsic motivation of students in choosing English as additional subject, the researcher got the result that show the extrinsic motivation is the highest reason chosen by the students when they chose English as their additional subject course at school than intrinsic motivation. It can be seen from the calculation scores of students intrinsic and extrinsic motivation that showed the total of mean score for extrinsic motivation is 47.5 and the total mean score for intrinsic motivation is 46.62. There are several extrinsic motivation from the students, for example the students prepare to learn English because they want to continue the study or get the works, go abroad and want to try to communicate with the foreigner.